Financial Dollarization and Central Bank Credibility - Cowan, Kevin (World Bank, Washington, DC, 2014)
Why do firms and banks hold foreign currency denominated liabilities? The authors argue that foreign currency debt, by altering the effect of a devaluation on output, has a disciplining effect when the Central Bank's objectives differ from the social optimum. However, under imperfect information, bad priors about the Central Bank induce excess dollarization of liabilities, which in turn limits the ability of the Central Bank to conduct an optimal monetary policy. In addition the economy may become stuck in a "dollarization trap" in which dollarized liabilities limit the ability of agents to learn the true type of the monetary authority. The model has clear-cut policy implications regarding the taxation of foreign currency liabilities as a way to encourage perfect information and avoid dollarization traps. Moreover, it reinforces the existing argument for Central Bank independence. Finally, the authors believe this model to be consistent with a growing empirical literature on the determinants of foreign currency liabilities and their relationships to Central Bank credibility.